Is There Space for Environmental Crimes Under International Criminal Law? The Impact of the Office of the Prosecutor Policy Paper on Case Selection and Prioritization on the Current Legal Framework - Mistura, Alessandra (Columbia Journal of Environmental Law, 2019)
The publication of a Policy Paper on Case Selection and Prioritization (the “Policy Paper”) by the Office of the Prosecutor (“OTP”) of the International Criminal Court (“ICC”) in September 2016 has reignited the longstanding discussion about the status of environmental crimes under international law. The Policy Paper expressed the intention of the OTP to consider, in the selection of crimes to be submitted to the jurisdiction of the ICC, those committed through, or resulting in, “the destruction of the environment, the illegal exploitation of natural resources or the illegal dispossession of land.” Such wording soon gained widespread attention, prompting many news outlets to declare that, from now on, the ICC would focus on prosecuting “environmental crimes.” The news sources’ enthusiasm, however, appears misplaced for several reasons. The first and foremost objection comes from a consideration of the ICC’s limited jurisdiction. In fact, this is strictly confined by the Rome Statute to the prosecution of “the most serious crimes of [international] concern,” currently identified as the genocide, war crimes, crimes against humanity, and aggression. The only reference to the environment that appears in the Rome Statute is included in Article 8.2(b)(iv), which lists among the activities constituting a war crime the act of, “[i]ntentionally launching an attack in the knowledge that such attack will cause . . . widespread, long-term and severe damage to the natural environment.” Given the limited attention to the environment, it would be difficult to maintain that the ICC has jurisdiction over “environmental crimes,” unless it could be shown that such jurisdiction either (i) may be derived implicitly from the current description under the Rome Statute of the crime of genocide, war crimes, and crimes against humanity, or (ii) has been extended by virtue of the creation of a new rule of international law, either customary or treaty-based. Most importantly, though, the possibility for the ICC to prosecute “environmental crimes” seems prevented by the failure to find a satisfactory definition for this notion. In the legal practice, this expression doesn’t have any authoritative meaning, as international treaties remain completely silent on the issue. And while several attempts at a definition have been made, as will be examined in more detail below, each of them raises several doubts and concerns. Many of the suggested definitions are, in fact, characterized by the lack of clarity with respect to the different sources from which the liability for “environmental crimes” arises and the specific consequences attached thereto. Indeed, such definitions indiscriminately consider: (i) the criminal liability of an individual arising from the breach of a rule of national environmental law; (ii) the criminal liability of an individual arising from the breach of a rule of international environmental law; and (iii) the liability of the State arising from the breach of a rule of international environmental law, whether customary or treaty-based. Of these three options, only the second would seem viable to serve as a foundation of the ICC’s jurisdiction over environmental crimes. The picture that emerges from the above-mentioned remarks shows that there is still widespread confusion on the consideration to be attributed to environmental crimes under international law, as well as the possibility of seeking prosecution for these crimes before an international tribunal. The purpose of this Note is to address such confusion and shed some light on the treatment that environmental crimes receive under international law. To do so, Part II provides a brief and general overview of the principles of international criminal law, with particular respect to: (i) its definition and the features distinguishing it from other overlapping branches of international law; (ii) the crimes that can be considered as belonging to its realm; and (iii) its sources and the possibility for it to evolve over time. Part III discusses what the term “environmental crime” means and which specific offenses, if any, may be punishable under international criminal law. In doing so, this Part will focus on the fundamental difference between “crimes under international law” and “transnational crimes” and the differences in the regimes applicable to each category. Lastly, Part IV discusses the current limits of the ICC’s jurisdiction and, in particular, the possibility of extending it to the prosecution of crimes, including environmental crimes not currently captured by the Rome Statute. Accordingly, this Part examines the potential impact of the Policy Paper in changing the scope of the ICC’s jurisdiction, as well as the relevance of other proposals advanced by academics and scholars to extend the ICC’s jurisdiction to environmental crimes. In this context, relevance will be given to the introduction of a crime of “ecocide” as a fifth crime against peace, and to the amendment of the description of the crimes provided under the Rome Statute through customary international law.